Determination of Tissue Distribution of Alisol G, a CB1R Antagonist, in Rats by Ultra-High-Performance Liquid Chromatography-Tandem Mass Spectrometry - Gao, Chen-Yu; Xi, Jian-Qiang; Song, Ding-Zhong; Yuan, Jie; Hao, Wu-Si; Cui, Zhong-Bao; Cheng, Zhi-Hong (Pharmaceutical Fronts, 2020)
Peripheral CB1R blockers without crossing the blood–brain barrier (BBB) have demonstrated therapeutic benefits in metabolic syndromes, including obesity. Among them is Alisol G, a tetracyclic triterpene from Alismatis rhizoma (zexie), which can effectively reduce the weight of obese mice. Results from CP55940-induced [35S] GTPγS cannabinoid-type 1 receptor (CB1R) binding assay show an IC50 of 34.8 μmol/L for Alisol G, implicating its role as a CB1R antagonist. The purpose of our study is to assess whether Alisol G could serve as a peripheral CB1R antagonist for obesity treatment. In this study, we build a simple, reliable, and sensitive method to detect the concentration of Alisol G in rat tissue by ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). The results showed that Alisol G was mainly distributed in intestinal midgut, mucosa and small intestine, with little brain exposure. We suggested that intestine may be the main acting sites of Alisol G. Through comparison of brain and blood concentrations of Alisol G, our data showed that Alisol G cannot penetrate the BBB easily. In conclusion, Alisol G may represent a peripheral CB1R antagonist for the further treatment of obesity.
Keywords: Alisol G; UHPLC-MS/MS; tissue distribution; blood–brain barrier